A unified measure of respondent privacy and model efficiency in quantitative RRT models. (3rd July 2018) - Gupta, Sat; Mehta, Samridhi; Shabbir, Javid; Khalil, Sadia
ABSTRACT: Model efficiency and respondent privacy are two important considerations while comparing two randomized response technique (RRT) models. Either the model efficiency level is kept fixed and the model offering greater privacy is preferred, or the privacy level is kept fixed and we prefer the model with better efficiency. In our current work, we propose a unified measure of model quality for a quantitative RRT model and compare several competing models with respect to this measure.